Kaji Pembuatan Kanvas Rem Sepeda Motor Bahan Komposit Dengan Filler Palm Slag - Frandi Barasa; Muftil Badri; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Brake pads have a very important role to become a major factor in driving safety. Brake quality depends on the constituent materials. Palm slag is one that has potential as a filler material for composite brake. Manufacture of brake pads in this study using the palm slag as a filler, phenolic resin as a binder, steel powder as reinforcing, graphite as a lubricant, alumina as an abrasive. In the manufacture of brake pads remains composition of materials used to variation the compacting and sintering temperature. This study will examine the wear rate and hardness in the brake pads against the brake commercial reference. Brake pads are made with palm slag initial compacting varied is 190 Bar and 380 bar and then proceed with the final compacting of 450 bar ± 2 minutes. Brake pads that have been heated to a temperature of 1500C using the heater. Brake pads that have been sintered variations to 1500C and 1700C. Brake pads that have sintered be tested for wear and hardness. Brinell hardness testing to get the highest hardness in the brake B is 15.35 BHN (kgf/mm2) commercial brake approaching violence. In dry conditions the wear testing found the smallest wear is approaching commercial brake brake B is equal to 4777 x 10-6 g/mm2.seconds with a braking time of 15.33 seconds and shortest braking distance is 63 meters. Keywords: Brake pads, palm slag, composite, sintering, compaction